Penerapan Program Literasi Numerasi Pada Pemecahan Masalah Matematika Kelas V Studi Kasus Di MIN 2 Mojokerto - Tiara Yuliarsih; Yhasinta Agustyarini (Jurnal Riset Madrasah Ibtidaiyah, 2023)
Numeracy literacy can help improve counting with examples of problems that exist in everyday life. Thus, it can be seen that the existence of analytic knowledge has an important meaning in learning mathematics in order to reason and help students solve problems. The purpose of this study is to describe and analyze the factors that support and hinder the implementation of the digital literacy program to solve the problems of grade 5 students in the MIN case study. 2 Mojokerto. This research method uses a qualitative approach to data collection, using observation, interview, and note-taking techniques. Thus, it can be concluded that the implementation of this digit literacy program has been done well, which can help improve the math problem-solving ability of 5th-grade students through 3 steps, which is the familiarization phase with the activity. Read aloud 15 minutes before studying. beginning, the development phase of literacy activities, where students have the opportunity to present the results of group discussions to develop student skills, and the stage where teachers learn using interesting concepts and strategies so that students can complete material taught through arithmetic knowledge.